2023
DOI: 10.2196/45437
|View full text |Cite
|
Sign up to set email alerts
|

Health Providers’ Perceptions and Experiences of Using mHealth for Chronic Noncommunicable Diseases: Qualitative Systematic Review and Meta-Synthesis

Yu Gu,
Yushan Guan,
Zhaolin Meng

Abstract: Background Mobile health (mHealth) technology has great potential for addressing the epidemic of chronic noncommunicable diseases (CNCDs) by assisting health providers (HPs) with managing these diseases. However, there is currently limited evidence regarding the acceptance of mHealth among HPs, which is a key prerequisite for harnessing this potential. Objective This review aimed to investigate the perceptions and experiences of HPs regarding the barrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(581 reference statements)
0
1
0
Order By: Relevance
“…Some doctors are unwilling to try this new technology because they are too busy with offline patients and fear potential risks ( Tables 7 , 8 ). These facilitating and preventive reasons have been documented in existing studies ( 26 , 27 ). In our study, we found that the patterns of social interactions might also affect the interviewees’ choice, which is rarely addressed in the extant studies ( 2 ).…”
Section: Resultsmentioning
confidence: 63%
“…Some doctors are unwilling to try this new technology because they are too busy with offline patients and fear potential risks ( Tables 7 , 8 ). These facilitating and preventive reasons have been documented in existing studies ( 26 , 27 ). In our study, we found that the patterns of social interactions might also affect the interviewees’ choice, which is rarely addressed in the extant studies ( 2 ).…”
Section: Resultsmentioning
confidence: 63%